An innovative gamification tool to enhance intercultural competence and self-efficacy among healthcare professionals caring for vulnerable migrants and refugees - Ruben Moreno-Comellas; Adria Murias-Closas; Stella Evangelidou; Lloy Wylie; Núria Serre-Delcor (BMC, 2024)
Abstract Background The growing number of vulnerable migrants and refugees (VMRs) in the European Union presents challenges to healthcare systems, emphasizing the need for enhanced intercultural competence training for healthcare professionals. Educational escape rooms, using gamification-based principles, may offer an innovative solution to improve these competencies. Objective This pilot study evaluates the acceptability and preliminary effectiveness of an educational escape room aimed at improving intercultural competence, self-efficacy, and knowledge among healthcare students and professionals caring for VMRs. Methods A pre-post, single-group pilot study was conducted with 101 healthcare students and professionals, recruited through convenience sampling. Participants engaged in an educational escape room simulating a migratory crisis, designed to foster collaborative problem-solving under pressure. A newly validated questionnaire was administered before and after the intervention to measure changes in intercultural competence, self-efficacy, and knowledge. Paired t-tests were used to analyze pre-post differences, and thematic analysis explored participant feedback on the learning experience and the acceptability of the intervention. Results Significant improvements were observed in intercultural competence (d = 1.13, p < 0.001), self-efficacy (d = 0.38, p = 0.001), and knowledge (d = 1.19, p < 0.001). Participants reported high engagement, satisfaction, and an enhanced understanding of healthcare challenges related to VMRs. The escape room was deemed acceptable. Conclusions This pilot study provides evidence of the acceptability and effectiveness of an educational escape room in enhancing intercultural competence, self-efficacy, and knowledge. Further research with larger, more rigorous studies is recommended to confirm these findings and explore scalability.